Risk factors of asymptomatic bacteriuria and fetomaternal outcome following treatment in early versus late gestation - Radhamani, Muthusamy; Amudha, Paneerselvam; Divya, Balasubramanian (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Asymptomatic bacteriuria (ASB) has higher incidence in pregnant than in non-pregnant women and is difficult to diagnose. It is associated with fetomaternal complications like prelabour rupture of membranes, preterm labour, low birth weight and increased perinatal mortality. The aim of this study is to analyse various risk factors and the maternal and fetal outcome following treatment of asymptomatic bacteriuria in early versus late gestation. Methods: This prospective study was conducted in Thanjavur Medical college and Hospital in 2019. The study population comprises all pregnant women attending antenatal clinic for their 1st antenatal visit. Results: Total of 800 antenatal women were enrolled in 2 groups based on gestational age <20 weeks (n=394) and between 28 to 32 weeks (n=406) at the time of their 1st antenatal visit. Incidence of asymptomatic bacteriuria was 13.6% and 84.4% were in the age group of 21-30 years. High prevalence was noted in primigravidae (47.7%) and in lower socioeconomic class (70.9%). Commonest organism isolated was E. coli (42.2%) and most of the organisms were sensitive to gentamycin (89.9%) and cefotaxime (84.4%). Despite treatment of asymptomatic bacteriuria, complications like anaemia, gestational hypertension & preterm labour were higher in late detection group than in early detection group. Conclusions: This study shows high prevalence of asymptomatic bacteriuria in pregnant women. The chances of developing maternal complications were significantly reduced after antibiotic therapy of asymptomatic bacteriuria. Hence, early screening and treatment of asymptomatic bacteriuria needs to be incorporated in routine antenatal care.